Pruning in the olive orchard [printed version also available in Arabic] - Abdine M.; Famiani F.; Cardone G.L. (Syrian national strategic plan for olive oil quality : final report, 2007)
The Italian cooperation project Technical assistance for the improvement of olive oil quality in Syria, carried out in 2004-06 period, included the improvement of the agronomic techniques and the transfer of technological innovation to Syrian olive growers. In this context, a specific activity was dedicated to olive pruning, also considering the use of machines to execute such a practice. In general, the development of mechanization can improve the competitiveness of Syrian olive growing in comparison to that of other countries and make Syria a country in the vanguard of the use of technologies. Technological innovation is not only aimed to increase the production, but also to reduce the costs and improve the quality of the product and of the working conditions of operators. The exchange of knowledge and experiences between the Italian and Syrian experts and the local farmers on pruning techniques was fruitful and mainly focused on the improvement of the production (quantity, quality and regularity) and phytosanitary state of the trees and the reduction of the occurrence of burns on branches (caused by intense solar rays in some regions) and cost for the execution of such a practice. In order to promote the technological modernization of the Syrian olive growing, demonstrations of mechanical pruning with pneumatic scissors and saws were performed. An evaluation to appraise the convenience of the use of machines for pruning and harvesting in the Syria conditions was also carried out.